NAVIGATING BANKRUPTCY RISK: THE ROLE OF GOVERNANCE IN BALI'S STATE-OWNED ENTERPRISES - Widnyana, I Wayan; Antari, Ni Putu Peri; Putri, I Gusti Agung Putu Sintia (Management Studies and Business Journal (PRODUCTIVITY), 2025)
This study aims to analyze the sustainability opportunities of State-Owned Enterprises (SOEs) operating in Bali using the Altman Z-Score bankruptcy prediction model. The research focuses on four strategic SOEs: PT PLN (Persero) Bali Distribution Main Unit, PT Angkasa Pura I (Persero) Ngurah Rai Airport, PT Pelindo (Persero) Benoa Branch, and Perum Bulog Divre Bali. These four SOEs were selected because of their vital roles in providing energy, air transportation, logistics, and food as the main pillars of Bali's economy, which is highly dependent on the tourism sector. The data used are secondary data in the form of financial reports for the 2019 - 2023 period, as well as macroeconomic data from BPS, Bank Indonesia, and the Bali Tourism Office. The analysis is conducted in two stages: (1) calculating the probability of bankruptcy using the Altman Z-Score, and (2) testing the influence of external factors (inflation, exchange rates, interest rates, tourism) and internal factors (liquidity, leverage, profitability) on the probability of bankruptcy using panel regression, as well as the role of corporate governance as a moderating variable. The results show that PLN Bali and Bulog Bali are in the safe zone, while Angkasa Pura I and Pelindo Benoa briefly entered the distress zone in 2020 due to a drastic decline in tourist visits, but began to recover in 2023. External factors include inflation, which has a significant negative effect, and tourism, which has a significant positive effect on the probability of bankruptcy, while exchange rates and interest rates are insignificant. Internal factors include only liquidity. Corporate governance has been shown to strengthen the influence of both external and internal factors in reducing the risk of bankruptcy. Overall, this study confirms that state-owned enterprises (SOEs) in Bali have a strong opportunity for sustainability if they can maintain liquidity, anticipate tourism fluctuations, and strengthen corporate governance. With adaptive strategies and government policy support, Bali's SOEs can transform into a resilient and sustainable driving force for the regional economy.